Health is Wealth – Toward a European Lead Market in Health Care - Felix Unger (Acta Medico-Biotechnica, 2021)
Human life represents the highest value. A healthy population is an indispensable prerequisite of a flourishing and wealthy society. There is no Wealth without Health. Any investment in the health sector is one of the most beneficial investments for the wealth of society. Economic growth is only possible with a healthy population. The role of European Union for creating a European Lead Market in Health care for modernization of medical care in Europe is presented.